Guideline For Developing the Bachelor of Arts Curriculum Department of Mahamakut Buddhist University Nakhon Pathom - Sahayapanyo, Phramahakhanob; Seangphrae, Janthima; Nathaponyo , Phramahaboonprasit; Dhammachotiko, Pramahasomsuk; Phuengphai, Suriyan (Journal of Dhamma for Life, 2026)
This research on developing a Bachelor of Arts in Buddhism curriculum focused on learning outcomes has two objectives: 1) to develop a Bachelor of Arts in Buddhism curriculum that emphasizes student learning outcomes, and 2) to evaluate the results of implementing this curriculum. The study population included individuals involved in the curriculum, such as students, course lecturers, and prison officials. The researcher employed research and development methods. The development of the Bachelor of Arts program in Buddhism, which focuses on student learning outcomes, identified five key components of curriculum development: 1) curriculum planning, 2) defining graduate characteristics, 3) establishing the philosophy and significance of the curriculum, 4) setting curriculum objectives, and 5) determining curriculum-level learning outcomes. These components guided the creation of a curriculum tailored for incarcerated students, aiming to produce graduates who possess knowledge and morality, as well as the ability to apply religious principles to transform behavior and refine character. This is especially important for prisoners preparing for reintegration into society as responsible and positive members. The implementation results of the Bachelor of Arts in Buddhism curriculum, which emphasizes student learning outcomes, revealed that the curriculum was revised in 2024 for use in the 2025 academic year at Bang Kwang Central Prison. The evaluation of the curriculum implementation was based on four components: 1) curriculum effectiveness, 2) the ability to design course learning, 3) learner outcomes, and 4) the satisfaction of all stakeholders involved in the curriculum.